2023
DOI: 10.1186/s12862-023-02108-y
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing 161 plant (streptophyte) mitochondrial group II introns into 29 families of related paralogues finds only limited links between intron mobility and intron-borne maturases

Abstract: Group II introns are common in the two endosymbiotic organelle genomes of the plant lineage. Chloroplasts harbor 22 positionally conserved group II introns whereas their occurrence in land plant (embryophyte) mitogenomes is highly variable and specific for the seven major clades: liverworts, mosses, hornworts, lycophytes, ferns, gymnosperms and flowering plants. Each plant group features “signature selections” of ca. 20–30 paralogues from a superset of altogether 105 group II introns meantime identified in emb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…Rice nad4 has four exons with three cis -splicing introns and nad5 has five exons with two cis -splicing introns (1 and 4) and two trans -splicing introns (2 and 3). Indeed, by amplifying fragments containing each of the introns in the nad4 and nad5 transcripts with specific primer pairs (Supplementary Table 1 ), we found that the first intron nad4i461g2 and nad5i230g2 (in group II-type introns, the intron name is composed of the gene name, the letter “i” for intron, and the insertion site in the orthologous gene of Marchantia polymorpha 45 , 46 , g2: group 2 intron) was retained, while the other introns in nad4 and nad5 were normally spliced in ospus1-1 sop10-1 plants (Figs. S 4 , S 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rice nad4 has four exons with three cis -splicing introns and nad5 has five exons with two cis -splicing introns (1 and 4) and two trans -splicing introns (2 and 3). Indeed, by amplifying fragments containing each of the introns in the nad4 and nad5 transcripts with specific primer pairs (Supplementary Table 1 ), we found that the first intron nad4i461g2 and nad5i230g2 (in group II-type introns, the intron name is composed of the gene name, the letter “i” for intron, and the insertion site in the orthologous gene of Marchantia polymorpha 45 , 46 , g2: group 2 intron) was retained, while the other introns in nad4 and nad5 were normally spliced in ospus1-1 sop10-1 plants (Figs. S 4 , S 5 ).…”
Section: Resultsmentioning
confidence: 99%